Niche specificity of two glypthelmins (trematoda) congeners infecting leptodactylus chaquensis (anura: Leptodactylidae) from Argentina - Hamann, Mónika Inés (2009)
Sixty-five specimens of the frog Leptodactylus chaquensis were infected by 2 Glypthelmins species (Glypthelmins repandum: 41%, and Glypthelmins palmipedis: 38%) in the small intestine. This study was designed to determine the site specificity of both species along the length of the small intestine by analyzing the distribution, niche overlap, morphological characteristics, and population dynamics. The location of G. palmipedis is very restricted, with the core infection site in the anterior small intestine. In contrast, G. repandum can be characterized as having an expanded niche within the small intestine. In single infections and with different intensities, individuals of both parasitic species showed preference for the anterior small intestine. In concurrent infections and with different intensities, the distribution of G. palmipedis did not change when G. repandum was present; however, displacement of G. repandum toward the middle of the small intestine was observed. Glypthelmins species used the same microhabitat and presumably the same food resource and were generally found to overlap more than expected by chance. This finding suggests the possibility of different feeding mechanisms given by differences in their pharynx size by 37%. Also, the coexistence of these could be associated with the differentiation of realized niches.